2014
DOI: 10.1038/onc.2014.309
|View full text |Cite
|
Sign up to set email alerts
|

The formyl peptide receptor 1 exerts a tumor suppressor function in human gastric cancer by inhibiting angiogenesis

Abstract: N-formyl peptide receptors (FPR1, FPR2 and FPR3) are involved in innate immunity, inflammation and cancer. FPR expression, initially described in immune cells, was later observed in non-hematopoietic cell populations and tissues. Several studies suggested a role for FPRs in the progression of various tumor histotypes, including gastric cancer (GC), for which a positive association with a specific FPR1 polymorphism has recently been described. We previously showed that FPRs are expressed on gastric epithelium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 35 publications
8
85
0
1
Order By: Relevance
“…6169 The role of FPR1 in tumor progression remains controversial as it has been associated with tumor invasion in colorectal cancer but with tumor suppression in gastric cancer. 70,71 As far as P2RY6 is concerned, Placet et al recently suggested its role in cancer cell survival. 72 Overall, these 13 chemotactic receptors and chemokines may constitute universal targets for cancer therapy.…”
Section: Resultsmentioning
confidence: 99%
“…6169 The role of FPR1 in tumor progression remains controversial as it has been associated with tumor invasion in colorectal cancer but with tumor suppression in gastric cancer. 70,71 As far as P2RY6 is concerned, Placet et al recently suggested its role in cancer cell survival. 72 Overall, these 13 chemotactic receptors and chemokines may constitute universal targets for cancer therapy.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is interesting that FPR1 silencing in GC cells significantly enhanced their tumorigenicity in mice because of augmented vessel density and tumor cell proliferation with high levels of HIF-1α and VEGF mRNA in xenografts tumor. Thus, FPR1 functions as GC suppressor by inhibiting tumor-induced angiogenesis (30). These observations, in contrast to those with FPR2 in GC, call for more careful evaluation of individual receptors in tumor growth, particularly in the context of microenvironment whether complex composition of tumor and stroma may determine the outcome of FPR signaling.…”
Section: Detrimental Effects Of Fprs Hijacked By Tumor Cellsmentioning
confidence: 99%
“…For instance, FPRs expressed by human gastric cancer cells, mediate epithelial-mesenchymal transition, cell proliferation, migration, and resistance to apoptosis (30). The prototype FPR, FPR1, selectively expressed by highly malignant glioblastoma multiforme (GBM) cells, responds to an endogenous chemotactic ligand anexin 1 (ANXA1) released by necrotic GBM cells (31).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, endocrine and metabolic diseases like diabetes and obesity fall within the ever-increasing group of inflammatory pathologies. All this without even considering cancer, where the nature of the inflammatory response is subverted and exploited by the proliferating tumoral cells [4][5][6].…”
Section: Introductionmentioning
confidence: 96%